1990
DOI: 10.1111/j.1442-200x.1990.tb00778.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibody‐Dependent Cellular Cytotoxicity and Natural Killer Activity Against HTLV‐1 Infected Cells

Abstract: Antibody‐dependent cellular cytotoxicity (ADCC) and natural killer (NK) ativity were examined using MT‐2 cells persistently infected by HTLV‐1 as target cells, and mononuclear cells as effector cells, from helathy one‐week‐old newborn babies, infants, children and adults. More than 10% of ADCC was observed in 17 newborn babies out of 22 (77.3%) and in all 67 healthy one‐month‐old babies to adults, by adding serum from anti‐HTLV‐1 positive carriers. When anti‐HTLV‐1 negative serum was added, less than 10% of AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
3
1
Order By: Relevance
“…Alternatively, interferon-a production induced by HIV-infected targets (26) may enhance NKC selectively in the neonate (16). Indeed, neonates' PBMC have been found to be as effective as adults' in NKC of human T-cell lymphotrophic virus-1-infected target cells (23). However, the striking difference we observed between adults and neonates in ADCC capacity suggests that a developmental defect in this mode of antiviral activity may exist in the human neonate.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Alternatively, interferon-a production induced by HIV-infected targets (26) may enhance NKC selectively in the neonate (16). Indeed, neonates' PBMC have been found to be as effective as adults' in NKC of human T-cell lymphotrophic virus-1-infected target cells (23). However, the striking difference we observed between adults and neonates in ADCC capacity suggests that a developmental defect in this mode of antiviral activity may exist in the human neonate.…”
Section: Discussioncontrasting
confidence: 53%
“…Because developmental defects in antiviral cytotoxicity have been observed toward cells infected with viruses other than HIV (17,23), we compared the effector cell capacity of leukocytes from healthy infants and adults in the NKC and ADCC HIV assay. Umbilical cord blood samples collected at the same time as blood samples from healthy adult volunteers were tested in pairs in the cytotoxicity assay to minimize artifacts from interassay variability.…”
Section: Hours Of Incubationmentioning
confidence: 99%
“…Viral infection significantly alters T-cell and dendritic cell functions, increases the frequency of intermediate and non-classical monocytes (pro-inflammatory monocytes), and decreases the frequency of classical monocytes that mediate apoptotic cell clearance and maintain tissue homeostasis [ 79 , 81 , 82 ]. The continuous but ineffective attempts of the immune system to clear HTLV-1 may result in chronic inflammation with exhaustion of both NK and CD8 cells, as reported in infected individuals with high virus burden [ 74 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. Although, in the current study, the depletion of monocytes in the blood was minimal, it is possible that tissue macrophage depletion was more pronounced, as has been reported [ 90 , 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, eliciting anti-HTLV-1 antibodies may be important for clearance by antibody-dependent cellular cytotoxicity (ADCC). An early study examining ADCC and NK cell activity from newborns, infants and adults suggests that these activities can protect against the transmission of mother-to-child [ 242 ]. A more recent study found that a neutralizing anti-Env antibody, LAT-27, induced ADCC, eliminating Tax positive cells and can contribute to the control of infection [ 243 ].…”
Section: Humoral Immunitymentioning
confidence: 99%